STUDY OF PRACTICAL AWARENESS TOWARDS THE LANGUAGE OF MASS MEDIA - Bharati, Reena; Ahmad, Jarrar (International Journal of Research -GRANTHAALAYAH, 2025)
Mass media have become the main sources of information, entertainment and education in modern society. These include newspapers, radio, television, internet and social media. Through these media, society receives many types of information, which influences the thinking and behavior of the society. Therefore, practical awareness towards the language of mass media is very important. Language is the soul of any mass media. It is not only a means of information, but also a way of expressing thoughts, feelings and cultures. The accuracy, clarity and communicability of the language of mass media have a deep impact on society. Therefore, it is necessary to increase awareness in the society about the language of these media. There are many aspects of behavioral awareness towards the language of mass media. The first aspect is correctness of language. It is necessary to take care of correctness of language in newspapers and television channels. Incorrect language not only hinders the correct communication of information, but also creates confusion in the minds of readers and viewers. For example, a wrong spelling or grammatical error in a news can completely change its meaning. Therefore, journalists and editors should take special care of correctness of language.